Laboratory assessment of two active ingredients for control of coptotemes gestroi (Isoptera: Rhinotermitidae) - Casarin, Fabiana Elaine [UNESP]; Costa-Leonardo, Ana Maria [UNESP]; Bueno, Odair Correa [UNESP] (My University, 2009)
The subterranean termite Coptotermes gestroi Wasmann (Isoptera: Rhinotermitidae) is a pest of major economic importance in urban environments of southeastern Brazil. Compared to using pesticides for termite control, termite bait products target termites more specifically and also address environmental contamination issues. In this point of view, we performed two different bioassays in order to evaluate the efficacy of boric acid and fipronil against different populations of C. gestroi. The results showed that concentrations between 2000 and 3000 ppm of boric acid caused approximately 100 percent mortality in termites. Concentrations between 0.01 and 0.0001 ppm of fipronil resulted in 100% termite mortality after 2 wk exposure. The data displayed a fast mortality of termites contaminated with fipronil, even with small concentrations, and therefore it is not a suitable product to be used in baits against C. gestroi. The present study showed a delayed toxicity of boric acid against the subterranean termite C. gestroi which suggests a need for further field tests.
Keywords: Bait; Boric acid; Control; Fipronil; Subterranean termites; Coptotermes gestroi; Isoptera; Rhinotermitidae